Multiple Hepatosplenic Abscesses From an Uncommon Pathogen in a Patient With Acute Promyelocytic Leukemia - Takao Goto; Akane Takamatsu; Ayako Nonaka; Hitoshi Honda (Annals of Internal Medicine: Clinical Cases)
We report a patient case of Magnusiomyces capitatus fungemia with multiple hepatosplenic abscesses. Magnusiomyces spp. are rare but emerging, opportunistic fungal pathogens causing potentially lethal invasive disease, especially in patients with neutropenia secondary to chemotherapy for a hematologic malignancy. Given the frequent use of echinocandins as empirical therapy for febrile neutropenia, extra caution should be exercised if culture results indicate the presence of a yeast other than Candida species.